2023
DOI: 10.1002/mnfr.202300432
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Study of Selenium‐Enriched Probiotics: From the Inorganic Se into Se Nanoparticles

Dan Xiao,
Tong Li,
Xin Huang
et al.

Abstract: Selenium (Se) is a momentous metallic element that plays an irreplaceable role in biochemical activities. Se deficiency remains a nutritional challenge across the world. Organic Se supplementation is the most effective treatment means for Se deficiency. Organic Se transformed from Se‐enriched probiotics show outstanding excellent properties in antibacteria, anti‐oxidation, anti‐inflammation, and immunoregulation. Studying the influencing factors for Se enrichment capacity and enrichment mechanisms of Se‐enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 117 publications
(154 reference statements)
0
0
0
Order By: Relevance
“…Due to its biological characteristics (resulting from its physical and chemical properties), Se is regarded as an element of great potential in various scientific fields, such as biomedical, food, agricultural, and environmental [6][7][8][9]. Selenium has not been classified…”
Section: Introductionmentioning
confidence: 99%
“…Due to its biological characteristics (resulting from its physical and chemical properties), Se is regarded as an element of great potential in various scientific fields, such as biomedical, food, agricultural, and environmental [6][7][8][9]. Selenium has not been classified…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been demonstrated that dietary Se deficiency induces oxidative stress, inflammatory damage, and apoptosis in a variety of tissues [14], and adversely affects broiler performance [15]. As a new form of Se supplement, selenium nanoparticles (SeNPs) can maximize the beneficial effects of Se because of their high surface activity and nanoscale effect [16]. Compared with organic and inorganic selenium, SeNPs have lower toxicity and higher biological activity [17].…”
Section: Introductionmentioning
confidence: 99%